Muddled through - Ross, Barbara, 1953- (Ross, Barbara, 1953- Maine clambake mystery., 2022)
"Mud season takes on a whole new meaning in the coastal town of Busman's Harbor, Maine, when local business owners sling dirt at one another in a heated feud over a proposed pedestrian mall...When Julia spots police cars in front of Lupine Design, she races over. Her sister Livvie works there as a potter. Livvie is unharmed...When a murder follows the break-in, it's up to Julia to dig through the secrets and lies to uncover the truth"--